Use and Awareness of Heated Tobacco Products in Europe - Odone, Anna; Tigova, Olena; Vardavas, Constantine; Gallus, Silvano; Borroni, Elisa; Liu, Xiaoqiu; Lopez, Maria José; Clancy, Luke; Lugo, Alessandra; Investigators, the TackSHS Project; Fernandez, Esteve; Piet A. van den Brandt; et al. (Journal of Epidemiology, 2022)
Background: Heated tobacco products (HTP) are new forms of tobacco consumption with limited information available on their use among the general population. Our objective was to analyze the prevalence and associations of use of HTP across 11 countries in Europe.Methods: Within the TackSHS Project, in 2017–2018 we conducted a cross-sectional study with information on HTP use in the following countries: Bulgaria, England, France, Germany, Greece, Italy, Latvia, Poland, Portugal, Romania and Spain. In each country, face-to-face interviews were performed on a representative sample of around 1,000 subjects aged ≥15 years, for a total of 10,839 subjects.Results: Overall, 27.8% of study participants were aware of HTPs, 1.8% were ever HTP users (ranging from 0.6% in Spain to 8.3% in Greece), and 0.1% were current users. Men were more frequently HTP ever users than women (adjusted odds ratio [aOR] 1.47; 95% confidence interval [CI], 1.11–1.95). Ever HTP use was inversely related to age (P for trend <0.001) and more frequent in ex-smokers (compared with never smokers, aOR 4.32; 95% CI, 2.69–6.95) and current smokers (aOR 8.35; 95% CI, 5.67–12.28), and in electronic cigarette past users (compared with never users, aOR 5.48; 95% CI, 3.46–8.68) and current users (aOR 5.92; 95% CI, 3.73–9.40).Conclusions: In 2017–2018, HTP use was still limited in Europe among the general population; however, the dual use of these products, their high use among younger generations, and the interest of non-smokers in these products are worrying and indicate the need for close monitoring in terms of prevalence and the characteristics of users.